Assessment of time limit at lowest speed corresponding to maximal oxygen consumption in the four competitive swimming strokes - Fernandes, R.; Cardoso, C.; Silva, J. A.; Vilar, S.; Colcao, P.; Barbosa, T.; Keskinen, K. L.; Vilas-Boas, J. P. (Biomechanics and Medicine in Swimming X, 2006)
Time limit at lowest speed of maximal oxygen consumption (Tlim-vV O2max) was characterized in the 4 swimming strokes, and related with V O2max and anaerobic threshold (AnT). 23 elite swimmers performed an incremental protocol for vV O2max assessment. 48 hours later, Tlim-vV O2max was assessed. V O2 was directly measured BxB (K4 b2, Cosmed, Italy) and AnT was assessed individually (YSI 1500L Sport, USA). Tlim-vV O2max values were 238.8±39.0, 246.1±51.9, 277.6±85.6 and 331.4+82.7 s in crawl, backstroke, butterfly, and breaststroke (no differences observed). No correlations were found between Tlim-vV O2max and V O2max, and AnT. However, inverse relationships were observed between Tlim-vV O2max and vV O2max (r=-0.63, p<0.01) and vAnT (r=-0.52, p=0.01), pointing out that the higher the velocities commonly related to aerobic proficiency, the lower the TLim- vV O2max.